A multi-functional nanoplatform for tumor synergistic phototherapy. (25th January 2016) - Zhang, Huijuan; Jiao, Xiaojing; Chen, Qianqian; Ji, Yandan; Zhang, Xiaoge; Zhu, Xing; Zhang, Zhenzhong
Abstract: Phototherapy, which mainly includes photothermal treatment (PTT) and photodynamic treatment (PDT), is a photo-initiated, noninvasive and effective approach for cancer treatment. The high accumulation of photosensitizers (PSs) in a targeted tumor is still a major challenge for efficient light conversion, to generate reactive oxygen species (ROS) and local hyperthermia. In this study, a simple and efficient hyaluronic acid (HA)-modified nanoplatform (HA-TiO2 @MWCNTs) with high tumor-targeting ability, excellent phototherapy efficiency, low light-associated side effects and good water solubility was developed. It could be an effective carrier to load hematoporphyrin monomethyl ether (HMME), owing to the tubular conjugate structure. Apart from this, the as-prepared TiO2 @MWCNTs nanocomposites could also be used as PSs for tumor PTT and PDT. Those results in vitro and in vivo showed that the anti-tumor effect of this system-mediated PTT/PDT were significantly better than those of single treatment manner. In addition, this drug delivery system could realize high ratio of drug loading, sustained drug release, prolonged circulation in vivo and active targeted accumulation in tumor. These results suggest that HA-TiO2 @MWCNTs/HMME has high potential for tumor synergistic phototherapy as a smart theranostic nanoplatform.